2022
DOI: 10.1093/bioinformatics/btac161
|View full text |Cite
|
Sign up to set email alerts
|

hacksig: a unified and tidy R framework to easily compute gene expression signature scores

Abstract: Summary Hundreds of gene expression signatures have been developed during the last two decades. However, due to the multitude of development procedures and sometimes a lack of explanation for their implementation, it can become challenging to apply the original method on custom data. Moreover, at present there is no unified and tidy interface to compute signature scores with different single sample enrichment methods. For these reasons, we developed hacksig, an R package intended as a unified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…To determine whether non-canonical module expression in untreated, non-metastatic primary tumors could serve as a biomarker of clinical outcome, we performed single sample gene set enrichment analysis (ssGSEA 44 ) on two independent datasets of pre-treatment primary tumors, the cancer genome atlas (TCGA) cohort of 445 patients with Stage I-IV colon or rectal adenocarcinoma 45, and an MSKCC cohort of 108 patients with locally advanced (Stage II-III) rectal cancers (LARC) 46 . Expression of non-canonical modules is (which was not certified by peer review) is the author/funder.…”
Section: Non-canonical Gene Expression Varies Across Patients and Is ...mentioning
confidence: 99%
“…To determine whether non-canonical module expression in untreated, non-metastatic primary tumors could serve as a biomarker of clinical outcome, we performed single sample gene set enrichment analysis (ssGSEA 44 ) on two independent datasets of pre-treatment primary tumors, the cancer genome atlas (TCGA) cohort of 445 patients with Stage I-IV colon or rectal adenocarcinoma 45, and an MSKCC cohort of 108 patients with locally advanced (Stage II-III) rectal cancers (LARC) 46 . Expression of non-canonical modules is (which was not certified by peer review) is the author/funder.…”
Section: Non-canonical Gene Expression Varies Across Patients and Is ...mentioning
confidence: 99%
“…Kaplan-Meier analysis showed that low-score LARCs had significantly lower DFS than high-score LARCs ( Figures 4D, F ). In contrast, Kaplan-Meier analysis showed there was no significant difference in survival between two groups based on the median immunophenoscore (IS) ( 23 , 24 ) ( Figures 4E, G ), suggesting that the score system of immunophenoscore failed to exploit the opportunity of predicting the LARCs prognosis.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, we investigated effects of the immune-associated configuration on patient survival by predicting the LARCs prognosis based on the IPS. Firstly, we calculated tumor purity scores (TPS) for patients in GSE3952 and GSE87211 by the R package hacksig ( 23 ). In GSE39582, the mean TPS of the high-score group was 0.338, and the low-score group was 0.388.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of fibroblast clusters was performed using principal component analysis (PCA) and hierarchical clustering using loge(1+ quantile normalized count) with the Euclidian distance used to calculate the distance matrix according to Ward's linkage 51 . Comparison to publicly available fibroblast/CAF signatures was performed by calculating combined z-scores 52 using the tidy framework hacksig 53 . Gene expression or combined z-scores were visualized using EnhancedVolcano 54 and/or pheatmap 55 .…”
Section: Rna Isolation Bulk Transcriptomics Cdna Synthesis and Quanti...mentioning
confidence: 99%